Elderly clothing business model transformation: a new review of the changes in service design thinking for product-service system design - Shaari, Nazlina; Wang, Mingrun; Ueda, Akira; Abidin, Sazrinee Zainal; Wan Omar, Wan Noor Faaizah; He, Yan (Taylor and Francis, 2025)
Today, elderly people are increasingly concerned about their quality of life and willing to spend on clothing to enhance their sense of wellbeing. Transforming the elderly clothing business model from traditional product-oriented business models to a service-oriented product-service system (PSS) is of great significance in creating maximum value for elderly people. Understanding the changes in service design thinking is crucial for guiding designers’ efforts in designing a service-oriented PSS for the elderly clothing industry. However, despite the extensive research conducted on the subject of PSS, little attention has been paid to identifying the changes in service design thinking. To fulfill this research gap, this study aims to identify the changes in service design thinking using a systematic literature review method. The research findings offer important knowledge on service design thinking, providing a basis for designers to develop accurate and foresighted PSS design thinking for the elderly clothing industry.